Promoting Effective Pain Assessment: A Quality Improvement Project - Durosier Mertilus, Dorothie S. (Clinical Journal of Oncology Nursing, 2025)
BACKGROUND: Pain management is a major healthcare concern, particularly for patients with cancer. About 51.6 million American adults experience chronic pain, with 17.1 million experiencing high-impact chronic pain. The staff nurses on the surgical oncology unit of a large community hospital did not fully adhere to updated evidence-based practice guidelines for pain management. OBJECTIVES: The purpose of this quality improvement project was to improve pain assessment practices on the surgical oncology unit of a 471-bed hospital. METHODS: Forty-nine nurses participated in this quality improvement project implemented across a three-month period. The intervention consisted of pre- and post-tests, two identical educational training sessions offered at different times for scheduling flexibility, interviews, and chart audits. The pre-/post-test design evaluated nurses' knowledge of pain assessment before and after the intervention. FINDINGS: This project found that expanding nurses' knowledge about pain assessment (t = 8.03, p < 0.001) resulted in increased adherence to national standards for pain management, including better charting practices. The pain assessment documentation rate increased from 18% to 29%.